Profil Kemampuan Pemecahan Masalah Soal HOTS Matematika Siswa SMP ditinjau dari Kemampuan Awal - Asdar; Alimuddin; Sukmawati Ali (Issues in Mathematics Education (IMED), 2022)
This study is presents to HOTS level problem solving ability profile in terms of initial ability. The type of research is descriptive qualitative research. This research was conducted in one of the junior high schools in Wakatobi Regency. The data collection techniques in by doing are written tests and interview guidelines. The instruments used are early mathematics ability tests, HOTS mathematics tests, and interviews. Participants in this study were 3 students with high initial ability, moderate initialability, low initial ability. The results showed characteristics of high students does not solve all problem solving. The medium student mastering all problem solving but are still wrong in writing answers related of problems the context. The Low sudent does not meet all of Polya problem solving